2010
DOI: 10.1523/jneurosci.3040-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Glycinergic Pacemaker Neurons in PreBötzinger Complex of Neonatal Mouse

Abstract: The preBötzinger complex (preBötC) is essential for normal respiratory rhythm generation in rodents, for which the underlying mechanisms remain unknown. Excitatory preBötC pacemaker neurons are proposed to be necessary for rhythm generation. Here we report the presence of a population of preBötC glycinergic pacemaker neurons. We used rhythmic in vitro transverse slice preparations from transgenic mice where neurons expressing the glycine transporter 2 (GlyT2) gene coexpress enhanced green fluorescent protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 45 publications
6
108
0
1
Order By: Relevance
“…Pre-BötC glutamatergic neurons have widespread projections [20] and are the primary source of rhythmic inspiratory excitatory drive. The cellular composition is heterogeneous and includes glutamatergic populations expressing neurokinin-1 receptors (NK1R), somatotstatin (SST), and the transcription factor developing brain homeobox 1 protein (Dbx1) [17,18], as well as subpopulations of inspiratory glycinergic [58,59] and GABAergic [60] neurons. The latter two types may provide inhibition of expiratory neurons during inspiration.…”
Section: Figurementioning
confidence: 99%
“…Pre-BötC glutamatergic neurons have widespread projections [20] and are the primary source of rhythmic inspiratory excitatory drive. The cellular composition is heterogeneous and includes glutamatergic populations expressing neurokinin-1 receptors (NK1R), somatotstatin (SST), and the transcription factor developing brain homeobox 1 protein (Dbx1) [17,18], as well as subpopulations of inspiratory glycinergic [58,59] and GABAergic [60] neurons. The latter two types may provide inhibition of expiratory neurons during inspiration.…”
Section: Figurementioning
confidence: 99%
“…RVLM presympathetic neurons with an inspiratory peak could be receiving input from IVLM cells that in turn receive input from inhibitory inspiratory neurons. All the postulated inhibitory inputs to the IVLM neurons (early inspiratory, inspiratory, or postinspiratory) are commonly found in the rVRG and pre-Bötzinger region, that is, in the immediate vicinity of the IVLM neurons (246, 296, 381). The late-expiratory peak observed in some presympathetic neurons when the respiratory drive is very elevated could plausibly originate from excitatory pfRG neurons with late-expiratory activity (246, 296, 381) (Fig.…”
Section: Central Cardiorespiratory Couplingmentioning
confidence: 99%
“…2 for other phenotypes). There were no inhibitory bursters [55] (the contradictory study [64] could have shown loss of either periodic synaptic drives [32, 52] or multi-cell synchrony [32]) and the kernel rhythm persisted after the inhibitory transmission blockade [65]. They may shape and/or tune the inspiratory activities in vitro.…”
Section: Section 3: the Physiology Of The Pre-bötzinger Complex From mentioning
confidence: 99%